Small business efficiency in the state of Kedah, Malaysia - Nor Hasni Osman; Abdul Aziz Jemain (Penerbit ukm, 2008)
This paper presents an empirical study on the efficiency of small businesses owned by Malays in Kedah, a state in the northern region of Peninsular Malaysia, wherein small businesses dominate the majority of commerce. There are five different types of main businesses, two from manufacturing and three from service sector. A study on the performance measurement using an efficiency technique of these businesses is sorely needed, since many Government agencies have provided continual help either financial or non-financial on a large scale, in order for these businesses to survive and compete in the commercial market. This study employs the data envelopment analysis (DEA), which is a non-parametric approach, to measure the performance of the subjects under study. DEA is widely use to measure the performance of organisations in the service industry. However, any organisation that is treated as a decision-making unit (DMU), including the manufacturing companies can use DEA technique in measuring their performance. Based on two basic models of DEA, almost 53% of DMUs from furniture production business are efficient. Whereas percentage of DMUs that are efficient for food processing, tailoring, food serving and grocery business are 42%, 41.7%, 34.1% and 33.3% respectively. The furniture production business also achieved the highest mean efficiency value compared to other type of business. The percentage of efficient DMUs and mean of efficiency had shown that the furniture production performs best in terms of efficiency level among the other four small businesses in Kedah